PERAN KELOMPOK SOSIAL DI DALAM FENOMENA ROJALI, ROHANA, DAN ROBELI (STUDI KASUS PADA SEBUAH MALL DI KOTA INDONESIA) - Bernardus Danny Harsono (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
The current social phenomenon emerging in shopping centers such as Rojali, Rohana, and Robeli is of particular concern. Previously, the Rojali, Rohana, and Robeli phenomena only occurred among a few individuals or social groups who tended to conduct research before purchasing goods. However, now, this social phenomenon is occurring on a large scale, resulting in a shift from shopping centers to tourist destinations. Clean, comfortable, and cool shopping conditions attract more visitors. Furthermore, the unstable economic situation is another contributing factor. This is also supported by the extraordinary development of technological sophistication. Furthermore, the convenience of shopping from home or the office has led to a shift in purchasing methods. This study aims to examine the role of social groups in the emergence of the Rojali, Rohana, dan Robeli social phenomena. The research method used is a qualitative method through observation and interviews. The results of this study indicate that social groups determine the direction of the Rojali, Rohana, and Robeli phenomena.